소련의 해체와 ‘지연된 내전’: 우크라이나 전쟁의 역사적 기원 - 윤종희 (Journal of Global and Area Studies , 8(1), 2024)
우크라이나 전쟁을 미국⋅EU와 러시아의 대리전으로 간주하는 지정학적 관점은 전쟁의당사자인 두 국가 사이의 쟁점을 종종 간과한다. 평화로웠던 양국의 관계가 2014년 후 급격히 악화된 이유는 무엇일까? 또 이 같은 변화는 과연 우발적⋅일시적인 것일까? 본 연구는소련의 역사를 아우르는 장기 시간대의 좌표평면 위에서 양국 관계의 변화를 조망한다. 소련이 해체될 때 양국은 영토, 인구, 자산 등을 재분할해야 했다. 하지만 유고슬라비아의 전철을밟지 않기 위해 경제적⋅외교적 방식으로 이 문제를 해결해왔다. 1990년대 혼란기를 거친후 러시아는 정치⋅경제적 구조에서 큰 변화가 없었던 반면, 우크라이나는 두 차례의 큰 정치위기(특히 2014년 마이단 정치혁명)를 거치면서 러시아에 적대적인 극우파가 권력을 장악했다. 극우파는 우발적으로 등장한 것이 아니라 오랜 역사적 기원을 갖는다. 키이우 정부의성격이 변함에 따라 양국 간 현안의 평화로운 해결은 더 이상 불가능해졌다. 게다가 키이우정부에 대한 미국⋅EU의 적극적인 지원이 극우파의 세력을 강화함으로써 우크라이나에서는정치가 실종되었다. 이번 전쟁이 어떤 식으로 종결되건, 양국 관계는 더 이상 과거로 돌아갈수 없을 것이다. Geopolitical perspectives that view the war in Ukraine as ‘a proxy war’ between the US-EU and Russia often overlook the issues between the two warring states. Why did the once peaceful relationship between the two countries turns hostile after 2014, and was this change accidental or temporary? This study examines the evolution of the bilateral relationship on a long-term time horizon that spans the history of the USSR. When the USSR dissolved, both countries had to repartition their territories, populations, and assets. However, in order to avoid following the fate of Yugoslavia, they have addressed this issue in an economic and diplomatic manner. After the turbulent 1990s, Russia’s political and economic structure remained largely unchanged, while Ukraine went through two major political crises (most notably the 2014 Maidan political revolution) that saw the far right, which is hostile to Russia, seize power. The far right did not emerge by accident, but has long historical origins. As the nature of the government in Kiev has changed, peaceful resolution of bilateral issues is no longer possible. Moreover, active US-EU support for the government in Kiev has strengthened the power of the far right, leading to the disappearance of politics in Ukraine. Regardless of how the war ends, relations between the two countries will never return to previous state again. KCI Citation Count: 0